Evaluation of the use of the myocardial performance index as a parameter of cardiac function in two experimental models of heart disease: myocardial infarction and pulmonary hypertension - Alexandre Luz de Castro; Patrick Turck; Angela Maria Vicente Tavares; Custódio José Gaspar; Alan Bahr; Alexsandra Zimmer; Tânia Regina G. Fernandes; Rafael Oliveira Fernandes; Vanessa Duarte Ortiz; Sílvio Tasca; Elissa Fernandes; Daniela Drosdowski; et al. (Pflügers Archiv - European Journal of Physiology, 2025)

Improving insect conservation management through insect monitoring and stakeholder involvement - Sebastian Köthe; Florian D. Schneider; Nikita Bakanov; Carsten A. Brühl; Lisa Eichler; Thomas Fickel; Birgit Gemeinholzer; Thomas Hörren; Alexandra Lux; Gotthard Meinel; Livia Schäffler; Christoph Scherber; et al. (Biodiversity and Conservation, 2023)
In recent years, the decline of insect biodiversity and the imminent loss of provided ecosystem functions and services has received public attention and raised the demand for political action. The complex, multi-causal contributors to insect decline require a broad interdisciplinary and cross-sectoral approach that addresses ecological and social aspects to find sustainable solutions. The project Diversity of Insects in Nature protected Areas (DINA) assesses insect communities in 21 nature reserves in Germany, and considers interactions with plant diversity, pesticide exposure, spatial and climatic factors. The nature reserves border on agricultural land, to investigate impacts on insect diversity. Part of the project is to obtain scientific data from Malaise traps and their surroundings, while another part involves relevant stakeholders to identify opportunities and obstacles to insect diversity conservation. Our results indicate a positive association between insect richness and biomass. Insect richness was negatively related to the number of stationary pesticides (soil and vegetation), pesticides measured in ethanol, the amount of area in agricultural production, and precipitation. Our qualitative survey along with stakeholder interviews show that there is general support for insect conservation, while at the same time the stakeholders expressed the need for more information and data on insect biodiversity, as well as flexible policy options. We conclude that conservation management for insects in protected areas should consider a wider landscape. Local targets of conservation management will have to integrate different stakeholder perspectives. Scientifically informed stakeholder dialogues can mediate conflicts of interests, knowledge, and values to develop mutual conservation scenarios.

Diversity of Insects in Nature protected Areas (DINA): an interdisciplinary German research project - Gerlind U. C. Lehmann; Nikita Bakanov; Martin Behnisch; Sarah J. Bourlat; Carsten A. Brühl; Lisa Eichler; Thomas Fickel; Matthias F. Geiger; Birgit Gemeinholzer; Thomas Hörren; Sebastian Köthe; Alexandra Lux; et al. (Biodiversity and Conservation, 2021)
Insect declines and biodiversity loss have attracted much attention in recent years, but lack of comprehensive data, conflicting interests among stakeholders and insufficient policy guidance hinder progress in preserving biodiversity. The project DINA (Diversity of Insects in Nature protected Areas) investigates insect communities in 21 nature reserves in Germany. All selected conservation sites border arable land, with agricultural practices assumed to influence insect populations. We taught citizen scientists how to manage Malaise traps for insect collection, and subsequently used a DNA metabarcoding approach for species identification. Vegetation surveys, plant metabarcoding as well as geospatial and ecotoxicological analyses will help to unravel contributing factors for the deterioration of insect communities. As a pioneering research project in this field, DINA includes a transdisciplinary dialogue involving relevant stakeholders such as local authorities, policymakers, and farmers, which aims at a shared understanding of conservation goals and action pathways. Stakeholder engagement combined with scientific results will support the development of sound policy recommendations to improve legal frameworks, landscape planning, land use, and conservation strategies. With this transdisciplinary approach, we aim to provide the background knowledge to implement policy strategies that will halt further decline of insects in German protected areas.